Six‐year experience with treatment of early donor‐specific anti‐HLA antibodies in pediatric lung transplantation using a human immunoglobulin‐based protocol. Issue 3 (7th January 2020) - Ius, Fabio; Müller, Carsten; Sommer, Wiebke; Verboom, Murielle; Hallensleben, Michael; Salman, Jawad; Siemeni, Thierry; Kühn, Christian; Avsar, Murat; Bobylev, Dmitry; Poyanmehr, Reza; Erdfelder, Caroline; et al.
Abstract: Objectives: Experience with the treatment of early donor‐specific anti‐HLA antibodies (eDSA) after lung transplantation in children is very limited. At our institution, we have treated patients with eDSA since 2013 with successive infusions of intravenous human immunoglobulins (IVIG), combined in some cases with a single dose of Rituximab and plasmapheresis (therapeutic plasma exchange [tPE]) or immunoabsorption. The aim of this study was to present the 6‐year results of IVIG‐based therapy in pediatric lung recipients. Methods: Records of pediatric (<18 years old) patients transplanted at our institution between 01/2013 and 03/2019 were reviewed. Outcomes were compared between patients with eDSA treated with IVIG (IVIG group) and without eDSA (control group). Median (interquartile range [IQR]) follow‐up amounted to 28 (12‐52) months. Results: During the study period, 66 lung‐transplanted pediatric patients were included, of which 27 (41%) formed the IVIG group and 38 (57%) the control group. Among the IVIG patients, 14 (52%) patients showed concomitant graft dysfunction (possible clinical antibody‐mediated rejection). The median time to eDSA detection was 24 (14‐63) days after transplantation. eDSA were cleared in 25 (96%) of the 26 patients which completed treatment. At 3 years, graft survival (%) was 73 vs 85 ( P  = .65); freedom (%) from chronic lung allograft rejection (CLAD) was 89 vs 78 ( P  = .82); and from infection 47 vs 31 ( P  = .15), in IVIG vs control patients, respectively. Conclusions: After lung transplantation, an IVIG‐based treatment for eDSA yielded high eDSA clearance. IVIG and control patients showed similar CLAD‐free and graft survival.